Circulating Inflammatory Factor Levels in the Early Phase of COVID-19 are Associated with the Progression of Respiratory Failure: A Single-Center Retrospective Study - Xiang X; Zhang Z; Liu Y; Xu W; Gong J; Yu S; Zhang L; Jiang T (Dove Medical Press, 2023)
Xiaoli Xiang,1,2 Zhicheng Zhang,1 Ying Liu,1 Wenxuan Xu,1 Ju Gong,3 Sheng Yu,4 Lan Zhang,5 Tingwang Jiang1 1Department of Key Laboratory, Affiliated Changshu Hospital of Nantong University, Changshu, People's Republic of China; 2Department of Ophthalmology, Affiliated Changshu Hospital of Nantong University, Changshu, People's Republic of China; 3Department of Emergency Medicine, Affiliated Changshu Hospital of Nantong University, Changshu, People's Republic of China; 4Department of Critical Care Medicine, Affiliated Changshu Hospital of Nantong University, Changshu, People's Republic of China; 5Information Center, Affiliated Changshu Hospital of Nantong University, Changshu, People's Republic of ChinaCorrespondence: Tingwang Jiang, Department of Key Laboratory, Affiliated Changshu Hospital of Nantong University, No. 68 Haiyu Nan Road, Changshu, Jiangsu Province, People's Republic of China, Tel +86 15995921425, Fax +86 512-52277250, Email jtwgyp@163.comPurpose: To evaluate the potential relationships between serum interleukin (IL)-2, IL-4, IL-6, IL-10, IL-17, interferon (IFN)-γ, and tumor necrosis factor (TNF)-α levels and occurrence of respiratory failure in patients with early-stage COVID-19 disease.Patients and Methods: We analyzed clinical characteristics, laboratory parameters, and immunoinflammatory markers in 302 patients diagnosed with SARS-CoV-2 infection who required hospitalization at Changshu Hospital of Nantong University. IL-2, IL-4, IL-6, IL-10, IL-17, IFN-γ, and TNF-α levels in the peripheral blood of patients hospitalized five days after disease onset were measured using multiplex bead-based flow fluorescent immunoassay (MBFFI).Results: Patients with respiratory failure had higher serum IL-4 [0 (0, 0.54) pg/mL], IL-6 [40.76 (12.33, 90.28) pg/mL], IL-10 [6.65 (4.12, 11.34) pg/mL], and IL-17 [9.48 (4.31, 12.13) pg/mL] levels than patients without respiratory failure (P=0.042, P< 0.0001, P=0.012, and P=0.036, respectively). Serum IL-2, IFN-γ, and TNF-α levels were not significantly different between the two groups. The occurrence of respiratory failure was positively correlated with sex (R=0.122, P=0.034), lactic acid (R=0.193, P=0.007), white blood cell count (R=0.121, P=0.038), erythrocyte distribution width (R=0.131, P=0.024), thyrocalcitonin (R=0.280, P< 0.0001), and D-dimer levels (R=0.214, P< 0.0001) but negatively correlated with oxygen partial pressure (R=− 0.208, P=0.004), oxygen saturation (R=− 0.220, P=0.002), lymphocyte count (R=− 0.129, P=0.026), and calcium (R=− 0.152, P=0.042). Among the immunoinflammatory biomarkers, the occurrence of respiratory failure was positively correlated with IL-4 (R=− 0.117, P=0.042), IL-6 (R=0.206, P< 0.0001), IL-10 (R=0.145, P=0.012), and IL-17 (R=0.121, P=0.036) levels.Conclusion: Serum levels of pro-inflammatory cytokines IL-6 and IL-17 and anti-inflammatory cytokines IL-4 and IL-10 were significantly elevated in patients with respiratory failure and weakly positively correlated with the occurrence of respiratory failure. Further studies are required to explore these key immune mechanisms to help clinicians better manage acute complications, long-term sequelae, and possible future COVID-19 variants and be flexible in managing future epidemics and similar public health threats.Keywords: COVID-19, respiratory failure, hypoxemia, biomarkers, cytokines, disease progression